Control of Mercury in Biological System - Singh, T.K.; Kumar, Ashok; Singh, Vidya (Asian Journal of Chemistry, 2010)
Mercury is transported in the ecosystem by precipitation from the atmosphere to soil and water, uptake by plants and animals providing a constituent of bio-geochemical cycle. We have worked to reduce the mercury ions from the cycle with help of oxygen/nitrogen- containing compounds suitable to the ecosystem and thus helpful in reducing the toxicity of the biological system. In this direction we have synthesized (DMF)2Hg(Ox)2, (DMA)2Hg(Ox)2 and (DMF)2Hg(OAc)2, (DMA)2Hg(OAc)2 and supported by electrical conductance measurement, where DMF = dimethyl formamide, DMA = dimethyl acetamide, Ox = oxalate ion, OAc = acetate ion.